Hiking the Absaroka-Beartooth Wilderness : a guide to 63 great wilderness hikes - Schneider, Bill (Falcon Guides, 2024)
"This guide, a thoroughly revised and updated edition of Hiking the Absaroka-Beartooth Wilderness, explores 62 trails in Montana's Absaroka-Beartooth Wilderness. The wilderness area, located north and northeast of Yellowstone, is renowned for its spectacular scenery and abundant wildlife"--